2020
DOI: 10.1007/s10708-020-10331-z
|View full text |Cite
|
Sign up to set email alerts
|

Movement and risk perception: evidence from spatial analysis of mobile phone-based mobility during the COVID-19 lockdown, Nigeria

Abstract: The emergence of COVID-19 across the globe prompted many countries to institute total lockdown or other models of mobility restrictions to mitigate the spread of the disease. On March 29th, Nigeria instituted a nationwide lockdown. It is pertinent to understand the pattern created by this lockdown. This could offer insights into how people perceive the hazard and the level of compliance across the States in Nigeria. Mobile phone-based mobility data and the number of new cases from the beginning to the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Of the 14 included studies, four studies included data from multiple countries across Europe, North America, Asia, Australasia and Africa [ 24 , 28 , 30 , 32 ]. Four studies were conducted in the United States of America (USA) [ 19 , 21 , 23 , 25 ] and other studies used data from Australia [ 31 ], Canada [ 26 ], India [ 29 ], Nigeria [ 27 ], South Africa [ 20 ] and Turkey [ 22 ] ( Table 1 ). All studies reported data from the first wave of the pandemic, with Google Mobility Scores included from January to August 2020, with most studies analysing data during the first two months of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 14 included studies, four studies included data from multiple countries across Europe, North America, Asia, Australasia and Africa [ 24 , 28 , 30 , 32 ]. Four studies were conducted in the United States of America (USA) [ 19 , 21 , 23 , 25 ] and other studies used data from Australia [ 31 ], Canada [ 26 ], India [ 29 ], Nigeria [ 27 ], South Africa [ 20 ] and Turkey [ 22 ] ( Table 1 ). All studies reported data from the first wave of the pandemic, with Google Mobility Scores included from January to August 2020, with most studies analysing data during the first two months of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Changes across most or all of the Google Mobility variables where reported separately by 9 of the 14 studies [ 19 21 , 25 , 27 , 29 32 ], whereas four studies only reported aggregated scores score [ 22 , 23 , 26 , 28 ] or just assessed changes in one variable [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ropkins and Tate [30] used data from several stations across the UK to examine the effect of lockdown on air pollutants while they used the backgrounds of the stations (Rural, Urban, and Traffic) to investigate the effect of traffic. Some studies have successfully used geolocation mobility data provided by Google and Apple as proxies of traffic to investigate movement and risk perception [35] and changes in air quality [36,37] during COVID-19 lockdown. Munir et al [38] in a study in Sheffield, UK highlighted the role of traffic in driving NO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The Google mobility data on stay-at-home activities reveals the level of public social distancing behaviour during the COVID-19 pandemic (e.g., Wang and Yamamoto, 2020;Noland, 2021;Yilmazkuday, 2021). Prior studies have suggested that an individual's mobility information reflects the degree to which his or her mobility is restricted during the pandemic; in our case, it captures individuals' risk perception during the epidemic (e.g., Kielland, 2016;Hsiehchen et al, 2020;Lawal and Nwegbu, 2020). After merging the mobility data with the demographic and COVID crisis data based on Federal Information Processing Standards, our final sample contains 1,776 counties.…”
Section: Introductionmentioning
confidence: 89%